Cardiotoxicity is mitigated after a supervised exercise program in HER2-positive breast cancer undergoing adjuvant trastuzumab - Jacquinot, Quentin; Meneveau, Nathalie; Falcoz, Antoine; Bouhaddi, Malika; Roux, Pauline; Degano, Bruno; Chatot, Marion; Curtit, Elsa; Mansi, Laura; Paillard, Marie-Justine; Bazan, Fernando; Chaigneau, Loïc; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Trastuzumab is used, alone or in conjunction with standard chemotherapy, to treat HER2-positive breast cancer (BC). Although it improves cancer outcomes, trastuzumab. can lead to cardiotoxicity. Physical exercise is a safe and effective supportive therapy in the management of side effects, but the cardioprotective effects of exercise are still unclear. Objectives: The primary aim of this study was to test whether trastuzumab-induced cardiotoxicity [left ventricular ejection fraction (LVEF) under 50%, or an absolute drop in LVEF of 10%] was reduced after a supervised exercise program of 3 months in patients with HER2-positive breast cancer. Secondary endpoints were to evaluate (i) cardiotoxicity rates using other criteria, (ii) cardiac parameters, (iii) cardiorespiratory fitness and (iv) whether a change in LVEF influences the cardiorespiratory fitness. Methods: 89 women were randomized to receive adjuvant trastuzumab in combination with a training program (training group: TG; n= 46) or trastuzumab alone (control group: CG; n = 43). The primary and secondary endpoints were evaluated at the end of the supervised exercise program of 3 months (T3). Results: After exercise program, 90.5 % of TG patients and 81.8% of CG patients did not exhibit cardiotoxicity. Furthermore, whatever the used criterion, percentage of patients without cardiotoxicity were greater in TG (97.6% and 100% respectively) than in CG (90.9% and 93.9% respectively). LVEF and GLS values remained stable in both groups without any difference between the groups. In contrast, at T3, peak V̇O2 (+2.6 mL.min-1.kg-1; 95%CI, 1.8 to 3.4) and maximal power (+21.3 W; 95%CI, 17.3 to 25.3) increased significantly in TG, whereas they were unchanged in CG (peak V̇O2: +0.2 mL.min-1.kg-1; 95%CI, -0.5 to 0.9 and maximal power: +0.7 W, 95%CI, -3.6 to 5.1) compared to values measured at T0. No correlation between LVEF changes and peak V̇O2 or maximal power was observed. Conclusion: A 12-week supervised exercise regimen was safe and improved the cardiopulmonary fitness in particular peak VO2, in HER2-positive BC patients treated with adjuvant trastuzumab therapy. The study is under powered to come to any conclusion regarding the effect on cardiotoxicity.